NASC's role in staff training and trainer development - Tuladhar, Subarna Man (2009)
An efficient and effective administrative machinery is a sine quo non for any economic development programme. Staff training is the obvious means to fulfil such a need. The main aim of this paper, as we perceive it, is to present a picture of a National level Training Institution like the Nepal Administrative Staff College (NASC) and relate it to public and non-public organizations which consume its services and development opportunities. This paper is split into three main parts, first, Introduction to NASC, second, General Staff Training and finally, Trainer Development. It makes an attempt to generate and promote ideas concerned with the concept, processes, and methods of training (To T included) and administration. - Reproduced.
Keywords: Training